El entorno familiar y su incidencia en el desarrollo socio afectivo de los niños y niñas del nivel inicial II del centro infantil Rinconcito Feliz del cantón Mejía, provincia de Pichincha, período lectivo 2013-2014 . Lineamientos alternativos - Punina Palacios, Janeth Irene (2014)
This research was part of an analytical, descriptive and explanatory study "FAMILY ENVIRONMENT AND ITS IMPACT ON SOCIAL EMOTIONAL DEVELOPMENT OF CHILDREN OF INITIAL CHILD CENTER LEVEL II" HAPPY CORNER " MEJÍA CANTON , Pichincha Province , LECTIVO PERIOD 2013-2014 " . ALTERNATIVE GUIDELINES, the same that was developed in accordance with the Rules of Academic Board of the National University of Loja. The general objective was raised for this research was: Educate parents about the importance of Family Environment in the Socio- emotional development of children of initial child center level II. Scientific, Inductive, Deductive, Descriptive and Statistical Model: methods were used. The techniques and instruments used were : Survey targeting parents or relatives of children of the Initial Level II "Rinconcito Happy " Children's Center Mejía Canton , Pichincha Province , in order to know the Family Environment , and . León Gross Ebee test applied to parents of children of the Initial level II "Rinconcito Happy" children's Center Mejía Canton, Pichincha Province, to meet the socio- emotional development. Analyzed the results of the survey concluded that teachers : 100% Parent have had conflicts due to lack of communication, 100 % due to economic problems , 50% for violence , 25% for alcohol , 10% by divorce , and 8% for any aspect mentioned. The Family environment is causing the children understand they are not alone, that belong to someone, they are attached forever to others, that they are valued. It is a source of emotional support, comfort, warmth, nutrition, protection and security. c. To support the research work of Ebee León Gross Test was applied to evaluate the Partner Development - Affective children with the following results : 68% of children surveyed have a development partner Affective Satisfactory , 28% Very Satisfactory and 8% unsatisfactory .